Coexistence with malicious and selfish nodes in wireless ad hoc networks: A Bayesian game approach. Issue 4 (December 2017) - Roles, Andrew; ElAarag, Hala
Mobile ad hoc networks are self-organized systems of nodes or installations, all cooperating to provide network functions such as routing and forwarding. Utilized in open environments, mobile ad hoc networks are vulnerable to attack by malicious nodes, causing harm or disorder. These nodes do not reveal their identities while disrupting service. Thus, early detection is important. The network may also contain selfish nodes, installations that choose to conserve power resources rather than provide network function. Identification of selfish nodes, too, is necessary so that functional nodes do not waste resources attempting to communicate with them. In this article, malicious and selfish node detection is modeled as a Bayesian game with imperfect information. In this attacker/defender game, the defender is unsure of the type of its opponent and must select strategies based on this incomplete information. Malicious nodes attempt to avoid detection by masquerading as regular nodes, providing useful network function at interval. This contribution to the network may, however, be entirely necessary in a mobile ad hoc environment with extremely limited resources and selfish nodes. In this article, we propose a more robust model than previous works that is capable of identifying any type of installation found in a mobile ad hoc environment. We demonstrate that selfish and malicious nodes can be successfully identified through our proposed attacker/defender game. In addition, we show that once identified, a malicious node may be exploited if the benefit it provides to the network is greater than the damage accrued. We evaluate our model using simulations. Our simulations show that our proposed model is beneficial because it improves network performance while conserving power resources.